Perbandingan Pembiayaan Murabahah & Musyarakah Menurun Untuk Produk Pembiayaan Konsumtif Pada Bank Syariah - Mohamad Heykal (Conference In Business, Accounting, And Management (CBAM), 2012)
Many financing that issued by Islamic banking sector in order to finance the various consumptive and productive product that issued by the Islamic banking. In this case, the majority contract that used is murabahah contract. On the other hand, there are also another contract that can be used for the consumptive product such as diminishing musharakah. This literature study research tried to shown and also compare this two kinds of financing scheme with the focus that financing scheme especially from Islamic banking to the consumptive sector will not burden the customer position. From this literature study it can be shown that the diminishing musharakah scheme could be one of the alternative financing from the Islamic banking.Keywords : Murabahah, margin, diminishing,musharakah, bank